2021
DOI: 10.1002/ls.1563
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of laser‐textured steel surfaces in unidirectional sliding line‐contact (block‐on‐ring)

Abstract: The following theoretical and experimental work presents a study on the influence of texture parameters on the tribological performance of dimpled steel surfaces. Different texture parameters were selected through hydrodynamic lubrication modeling based on the two‐dimensional Reynolds equation and literature search. For the experimental work, microscopic spherical cavities (i.e., dimples) were created by laser on 25 mm steel discs. The textured specimens were tested in a unidirectional sliding line‐contact blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Similar studies with respect to circular texture patterns using LST techniques were studied, and the improvement in the load-bearing capacities of these dimples at the HL regime was shown. The main reason for this improvement was the capacity to withstand the lubricant at the sliding interface, which reduced COF values in the full-film lubrication regimes [31]. Additionally, the solid lubricant properties of the MoSeC are an interesting characteristic due to the molecular structures of the transition metal atoms.…”
Section: Block On Ringmentioning
confidence: 99%
“…Similar studies with respect to circular texture patterns using LST techniques were studied, and the improvement in the load-bearing capacities of these dimples at the HL regime was shown. The main reason for this improvement was the capacity to withstand the lubricant at the sliding interface, which reduced COF values in the full-film lubrication regimes [31]. Additionally, the solid lubricant properties of the MoSeC are an interesting characteristic due to the molecular structures of the transition metal atoms.…”
Section: Block On Ringmentioning
confidence: 99%
“…Surface texturing is a manufacturing technology used to create dimples or grooves on the material's surface [20]. Therefore, it has been applied in different fields to obtain different functional surfaces, namely for aesthetic purposes, and to improve the thermal efficiency of components as well as their tribological behaviour [21][22][23]. The laser texturing of metallic surfaces has been performed and commercial products have been successfully trialled in the automotive industry [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been used to modify the surface properties of steel components such as sandblasting, chemical etching, deposition of coatings, electrode discharge machining (EDM), electrochemical machining (ECM), and texturing by electron beam, electric arc, or laser ablation [7][8][9][10]. Laser surface texturing, in particular, has been an e cient surface modi cation technique to improve the thermal e ciency of components, as well as their tribological behaviour [11,12]. However, just one study on the laser surface texturing of 420 stainless steel was found in the literature.…”
Section: Introductionmentioning
confidence: 99%